Analisa Kinerja Keuangan Kppri Dengan Pendekatan Laporan Keuangan Pada Kppri - Dwi Dewianawati (Politeknik Ganesha Medan, 2022)
Economic development in today is very fast, this can be seen from the changes that are happening now, these changes are the impact of economic globalization which is none other than trade liberalization and free market economic investment, as a result of that free market is likely to occur competition free tight, so the strong party and high purchasing power will dominate the market and become a winner in the competition and vice versa, the weak party with low purchasing power will automatically be excluded from the scope of competition and will be a passive audience in trading. From the ratio analysis of financial statements. KPRI can be seen in comparing the number of assets with the ability to meet short-term obligations turned out to be less good because it is still far from industry standards, and in the ability to pay all financial obligations both short-term and long-term are also still liquid, but in obtaining income net every year, in 2016-2020 KPRI was considered able to obtain high profits. Because in each year the income earned is increasing. And in generating a net profit KPRI is considered sufficient because it is measured by its effectiveness in investing its capital throughout all assets. Based on the results of KPRI performance measurements using the concept of ratio analysis of financial statements that have been carried out, it results in a satisfactory total performance measurement. Strategic planning that has been made is carried out to the fullest so that the cooperative's performance is in accordance with the vision and mission of KPRI.